2013
DOI: 10.1186/1471-2458-13-1
|View full text |Cite
|
Sign up to set email alerts
|

A commentary on studies presenting projections of the future prevalence of dementia

Abstract: BackgroundPopulation ageing over the first half of this century is likely to lead to dramatic increases in the prevalence of dementia. This will affect all regions of the world, but particularly developing regions. Dementia projections have been used extensively to support policy. It is therefore important these projections are as accurate as possible.DiscussionIn this paper we provide a commentary on studies projecting the future prevalence of dementia for the world or for individual continents. We identify s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

92
1,012
16
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,004 publications
(1,124 citation statements)
references
References 24 publications
(34 reference statements)
92
1,012
16
4
Order By: Relevance
“…Inconsistent evidence makes it difficult to justify the claim that LB women have fewer reproductive behaviours than heterosexual women. Previous systematic reviews on the health of LB women have considered smoking cessation,24 mental health,25 substance abuse,26 weight,4 breast cancer27 and cervical screening 7. One narrative review concluded there was little to no published literature on incidence and prevalence of endometrial and cervical cancer in LB women, and that further research was necessary to fill the knowledge gap 28…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistent evidence makes it difficult to justify the claim that LB women have fewer reproductive behaviours than heterosexual women. Previous systematic reviews on the health of LB women have considered smoking cessation,24 mental health,25 substance abuse,26 weight,4 breast cancer27 and cervical screening 7. One narrative review concluded there was little to no published literature on incidence and prevalence of endometrial and cervical cancer in LB women, and that further research was necessary to fill the knowledge gap 28…”
Section: Introductionmentioning
confidence: 99%
“…Third, current dementia projection methods are typically based on the assumption that certain factors will remain stable over time, such as age-specific dementia prevalence (ADI, 2015), mortality, and dementia risk factors (except demographics) (Rocca et al, 2011). Such projections do not adequately account for "changing patterns in risk factors" (Norton et al, 2013), i.e. trends in population-level factors, Time trends in dementia incidence and prevalence 1645 that can be accounted for in studies based on administrative health data.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] It is associated with significant disability for patients, considerable caregiver burden and increased use of health and social services. [6][7][8][9][10] The United Kingdom estimates forecast an increase from approximately 750,000 individuals currently affected to more than 1.7 million by 2051 as the population ages.…”
Section: Introductionmentioning
confidence: 99%